2020
DOI: 10.32553/ijmbs.v4i1.840
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Profile in Primary Hypothyroidism

Abstract: Introduction: Thyroid function disorders are among the most common endocrine diseases. Females are affected more than males, especially during the reproductive age. Hypothyroidism is the most prevalent type with a reported frequency of 2–5% worldwide. Thyroid hormones are essential for virtually all body tissues. So deficiency may affect hematopoiesis in bone marrow and eventually hematopoietic cells. Hematological abnormalities have frequently been reported in thyroid disorders. Anemia is frequently observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…We found that females have more prevalence of thyroid disorder than males under the circumstances of thyroid dysfunction at a young age (<20 and 20-30 years), as shown in Table 3. Many researchers have reported the correlation between anemia and thyroid dysfunction, and they estimated that more than 50% of patients have blood abnormalities with thyroid dysfunction, particularly with subclinical hypothyroidism [12,13,[15][16][17]40,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that females have more prevalence of thyroid disorder than males under the circumstances of thyroid dysfunction at a young age (<20 and 20-30 years), as shown in Table 3. Many researchers have reported the correlation between anemia and thyroid dysfunction, and they estimated that more than 50% of patients have blood abnormalities with thyroid dysfunction, particularly with subclinical hypothyroidism [12,13,[15][16][17]40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Study subjects with thyroid dysfunction were divided into four categories [5,[24][25][26] as follows: (a) primary hypothyroidism: serum TSH > 4.94 µIU/mL and FT4 < 0.7 ng/dL; (b) primary hyperthyroidism: serum TSH < 0.35 µIU/mL and FT4 > 1.48 ng/dL; (c) subclinical hyperthyroidism: normal FT4 (0.7-1.48 ng/dL) and serum TSH below the lower limit of the reference range (<0.35 µIU/mL); (d) subclinical hypothyroidism: normal FT4 (0.85-1.4 ng/dL) and serum TSH higher than the upper limit of reference range >4.94 µIU/mL. Generally, anemia is defined by low Hb (<12 g/dL in females and <13.5 g/dL in the male), where the subdivision of anemia includes a microcytic hypochromic, which comes with low MCV and low MCH and normocytic normochromic with normal MCV and normal MCH, respectively [12][13][14][15].…”
Section: Precipitant and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anemia and other blood abnormalities are common in thyroid function abnormalities mainly hypothyroidism, and most patients are improved after thyroid hormone replacement and normalization of the thyroid function [ 4 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most authors recommend treatment with iron supplementation in those patients, patients who were treated with iron supplement alone without treatment with thyroxin showed lower response rates than combination therapy. Some population based studies confirmed that there is no significant association between anemia and thyroid dysfunction, this suggest that the results showed variation and this association is not constant [ 4 , 14 , [17] , [18] , [19] , [20] ].…”
Section: Discussionmentioning
confidence: 99%